Bohring Opitz Syndrome: A case of a rare genetic disorder (Indian Journal of Case Reports, 2018)
Bohring-Opitz syndrome (BOS) is a rare genetic disorder, characterized by feeding difficulties, developmental delay, microcephaly, micrognathia, limb anomalies, and typical phenotypic facial features. The cause of the syndrome is identified as de novo heterogeneous mutations in the ASXL1 gene, but other mutations have been described in some patients. Most patients die in early childhood due to infections and comorbidities. As molecular confirmation by genetic studies is not always possible, this syndrome is diagnosed on the basis of distinctive clinical features. We report a case of the 6-month-old male child having gastroesophageal reflux and physical features of microcephaly, sloping forehead, sparse hair, craniosynostosis, telecanthus, hypertelorism, prominent eyes, posteriorly rotated ears, high-arched palate, micrognathia, pes planus, and typical BOS posture. A multidisciplinary approach is required for managing these patients.